What is Interactive Multimedia?, and How Much Effect on Enhancement of Learning Results? - Zul Afdal (P3M STKIP 'Aisyiyah Riau, 2016)
The purpose of this study is to explain theoretically about interactive multimedia and test its effect on the improvement of student learning outcomes. Based on interviews and literature review, this research hypothesis states that interactive multimedia has an effect on the improvement of learning outcomes. The population in this study is all students of Vocational High School accounting. The sample in this study were accounting students 1 and accounting students 2 academic year 2014/2015 which amounted to 70 people consisting of 2 classes. Instrument of data collecting used is student cognitive test which amounted to 20 item question. The hypothesis was analyzed with the General Linear Model (GLM) Univariate with the help of SPSS 17.0. The result of hypothesis analysis can be concluded that: There is influence of interactive multimedia usage to accounting student learning result with significance (p = 0,000).